The Role of Guidance and Counseling Teachers in Handling Student Learning Problems at State Islamic Senior High School 1, Ternate City - Widya Ali; Mawardi Djamaluiddin; Jainab Canu (Golden Ratio of Social Science and Education, 2026)
Student learning problems are one of the main challenges in the implementation of education in Madrasah Aliyah (Islamic Senior High School), which can impact students' academic achievement and psychological development. Guidance and Counseling (BK) teachers play a strategic role in helping students overcome these problems through appropriate guidance and counseling services. This study aimed to analyze the role of BK teachers in addressing student learning problems at Madrasah Aliyah Negeri 1 Ternate City using a person-centered approach. This study employed a descriptive qualitative approach. Data were collected through in-depth interviews, observations, and documentation involving BK teachers and students who experienced learning problems. Data analysis was carried out thematically through the stages of data reduction, data presentation, and conclusion drawing, and its validity was tested through the triangulation of sources and techniques. The results show that BK teachers apply a person-centered approach by building empathetic counseling relationships, accepting students without stigma, and encouraging student independence in finding learning solutions. This approach contributes to increased learning motivation, academic self-confidence, and student awareness of learning strategies that are appropriate for their personal conditions. However, the implementation of BK services still faces obstacles, such as limited service time and stigma towards BK services. This study emphasizes the importance of strengthening person-centered guidance and counseling services within the context of madrasas.